A Brief Research Report on the Perception and Satisfaction of Italian University Students With Disabilities and Specific Learning Disabilities at the Emergency Remote Teaching During the COVID-19 Lockdown - Carpinelli, Luna; Bruno, Giorgia; Savarese, Giulia (Frontiers in Education, 2021)
This study surveyed the perceptions and satisfaction of university students with disabilities and Specific Learning Difficulties (SLDs) with the Emergency Remote Teaching (ERT) delivered by the University of Salerno (Italy) in the lockdown phase (period March–April 2020) following restrictions due to the COVID-19 pandemic. The answers obtained from the survey questionnaire administered remotely showed that only 21% of the students with disabilities/SLDs were dissatisfied with the study method used due to difficulties encountered, including those related to the weakness of the technological infrastructure. In addition, important social and emotional aspects emerged as a consequence of the absence of interactions and relationships with both the faculty and the peer group.